University Students' Procrastination: A Mathematical Model (Case Studies: Student in Mathematics Department Universitas Negeri Padang) - Rara Sandhy Winanda; Akira Mikail; Defri Ahmad; Dina Agustina; Rahmawati Rahmawati (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
Mathematical modeling of procrastination was carried out on students in the Mathematics Department at Universitas Negeri Padang. Procrastination is the tendency to delay work and can be contagious among students. Mathematical modeling of procrastination aims to show the spread of procrastination among students. The SEIR compartment model was applied in this study. From a total of 1,154 population members, 93 samples were randomly selected and were given a questionnaire to estimate the parameter values in the model. A couple of steady states appear in the model. The free disease steady state has a biological meaning since all the variables are real, while the endemic steady state is surreal in biological terms. The number of its basic reproduction number, from which the parameter values are derived from the primary data, indicates stability analysis near the free disease steady states. The result shows that procrastination is spread among students in the population, with the number of Ro is 1,009.